PENGEMBANGAN SSP FISIKA MODEL INKUIRI TERBIMBING BERBANTUAN EDMODO POKOK BAHASAN FLUIDA STATIS - Maulida, Dina Rahmah; Suparwoto, Suparwoto; Pramudya, Yudhiakto (Universitas Muhammadiyah Semarang, 2018)
This study aims to develop physics Specific Pedagogy (SSP) Subjects of Edmodo-assisted guided inquiry model of static fluid subject and describe the feasibility of the products it produces. The research design used in this study is the 4-D Research and Development (R & D) model, with define, design, develop and disseminate stages. In this regard, disseminate merely provides products to schools. Research subjects in class XI MIPA 5 as part of a limited trial of the products produced. The instrument used in this study is the SSP validation sheet which includes syllabi, RPP, and LKPD. Data collection is done using validationsheets and questionnaires. The data analysis technique used is by describing the validation results forwarded by calculating CVR (Content Validity Ratio) and CVI (Content Validity Index). To determine the reliability of the product, PA (Percentage Agreement) is used. Inthis study, the results of the validation of the SSP obtained include the syllabus of 3.75, RPP 3.68, and LKPD 3.60 categorized as valid with the PA value for syllabus of 96.88%, RPP 97.26% and LKPD 97.19 % categorized as reliable. The CVI value for the syllabus is 0.60,RPP 0.55, and LKPD 0.36. Whereas CVR assessment is categorized as valid. So that it can be concluded that, the Physical Specific Pedagogy (SSP) subject of edmodo assisted inquiry inquiry on the topic of static fluid is feasible to be used in learning. Keywords: Subject Specific Pedagogy, Guided Inquiry, Edmodo, Static Fluid